Effect of Farmers' Socioeconomic Characteristics on Access to Agricultural Information in Gwagwalada Area Council, Abuja - Cynthia Achichi,; Sennuga, Samson Olayemi; Osho-Lagunju, Bankole,; Alabuja Funso Omolayo, (Discoveries in Agriculture and Food Sciences, 2022)
This study was done to examine the information sources accessible to farmers in the Gwagwalada Area Council, Abuja. All farmers in the study region made up the population, and a sample size of 120 respondents were randomly chosen from this group. A well-structured questionnaire was used to gather data for this study's main sources. Descriptive statistics and the logit regression analysis model were used to evaluate the data. The findings showed that the majority of farmers (42.5%) were between the ages of 36 and 50, were married, and had households with 11 to 20 people. Additionally, the farmers (43%) make between N100,001 and N500,000. Results of the research revealed that farmers have access to some information such as information on fertilizer application, land preparation, improved varieties, fertilizer rate application, pest and diseases, market information and storage and processing. Few farmers had access to information on climate change, proper irrigation and farm machineries. The major source of information was radio, friend and relatives, farmers association and television. Education, marital status, and property size were all significant at the 5% level of probability, according to a logistic regression analysis of socioeconomic characteristics. The study came to the conclusion that radio, family, and friends are the most accessible sources of knowledge. The study comes to the conclusion that socioeconomic factors like gender, employment, annual revenue, farm experience, education, and farm are important for farmers. In order to motivate farmers to purchase some of the facilities that depend on these amenities to operate and provide access to information, it was suggested that the government make basic services like electricity and internet connections more affordable.